Standardized assessment domains as predictors of prescription of trauma-focused treatment for youth in out-of-home care. (November 2020) - Verbist, A. Nathan; Winters, Andrew M.; Collins-Camargo, Crystal; Antle, Becky F.
Highlights: Using a standardized assessment tool enables CW and BH providers to communicate. CANS assessment domains were associated with a prescribed trauma-focused treatment. Youth with severe trauma were more likely to be prescribed trauma-focused treatment. Some youth with trauma symptoms were not prescribed trauma-focused treatment. Findings suggest training and supervision implications for CW and BH providers. Abstract: It has long been recognized that youth entering out-of-home care have traumatic experiences and their associated effects on emotional and behavioral wellbeing may be unrecognized, overlooked, or untreated. An assessment to identify youth needs is vital as an initial step to youth in out-of-home care receiving needed treatment. Standardized assessments in particular can serve as an effective starting point in addressing the needs of these youth. This study explored if domains of the Child and Adolescent Needs and Strengths assessment were associated with a prescribed trauma-focused treatment. Bivariate and multivariate analyses were conducted utilizing a cross-section of child welfare involved youth who were part of the out-of-home care system and received a CANS assessment. Results from this study suggest the most predictive CANS domains were 'emotional behavioral needs' followed by 'caregiver/ needs and strengths'. There was a sizeable portion of youth in the study with identified trauma-related symptoms who were not prescribed a trauma-focused treatment; which is consistent with prior research and suggests traumatized youth in out-of-home care are undertreated. More investigation of youth who have been assessed to have trauma-related needs, but who have not been assigned a trauma-focused treatment is needed. Findings have training and supervision implications for child welfare and behavioral health providers, and can aid in understanding the characteristics and needs of the youth served. Using similar language from standardized assessments allow child welfare and behavioral health workers to better communicate and collaborate to serve youth. Findings from this study promote evidence-informed practice in child welfare and behavioral health in order to better serve children and families.